Exploring the Novel Input Attributes Affecting eWOM - Hussain, Safdar; Huang, Kaishan; Ilyas, Zahida; Niu, Ben (Frontiers in Psychology, 2020)
Electronic word of mouth (eWOM) has taken significant importance in online communities, which is a more influential source for instant information on the internet. The purpose of this study is to examine the eWOM input attributes linked to consumers’ information adoption behavior in the context of information related interaction. This study conducted a structural equation modeling approach by choosing 466 active participants through a non-probability purposive sampling from Fujian and Guangdong provinces of China. The results revealed that eWOM input attributes such as online opinion seeking, source credibility, and social tie have positively influenced information related interaction. An individual’s perception enhances the performance of products or services referred by perceived values, which is an essential predictor of information adoption. Furthermore, information related interaction and information usefulness are the key eWOM message characteristics related to information adoption on the internet. This study contributes to the eWOM input attributes and message characteristics literature by exploring information related interaction as a new mediator to consumers’ online information adoption. The authors drew the suggestions for practitioners to develop appropriate strategies dynamically in response to consumers’ behavioral concerns by using comparative and contextual online platforms, which will help online consumers in their decision-making.